Chitosan molecular weight effect on starch-composite film properties. (October 2015) - Bof, María Julieta; Bordagaray, Valeria Carina; Locaso, Delia Elisa; García, María Alejandra
Abstract: The aim of this work was to prepare and characterize composite films based on chitosan (CH) and corn starch (CS), analyzing the inﬂuence of the chitosan molecular weight (MW) on film structure and functional properties. Three chitosan products were characterized and classified as low (LMW), medium (MMW) and high (HMW) according to its MW. Rheological behavior of filmogenic solutions depend on CH-MW from Newtonian to pseudoplastic one. Chitosan based film physicochemical properties were strongly affected by its molecular weight: the lower the MW the higher the color differences and film solubility. SEM observations demonstrated that plasticized chitosan films exhibited homogeneous structures, the higher the MW the more compact is the structure and the lower is the water vapor permeability (WVP, 4.55 ± 0.6 × 10 −11 g/m s Pa.). Likewise, CH and CS were compatible polymers which led to the development of homogeneous blend films. Polymer interactions were evidenced in FTIR spectra by the shifts observed within the region of 1500–1700 cm −1, which reduce the hydrophilic groups' availability of chitosan matrices, leading to a reduction in WVP of composite films. Mechanical properties of the developed films were performed through different complementary tests. Chitosan MW affects both the type and number of interactions, which determine the matrix structure and characteristics. In HMW-CH matrix polymer–polymer interactions are favored, leading to strong and resistant matrices with high dynamic elastic modulus values. Meanwhile, in LMW-CH one, polymer-plasticizer and polymer–solvent interactions became important and the development of high extensible and soluble materials is privileged. Graphical abstract: Highlights: Film based on different molecular weight chitosan and corn starch were developed. Chitosan molecular weight affected both physicochemical and final film properties. The interrelation between film structure and its properties was established. High molecular weight chitosan matrices were rigid and resistant exhibiting low WVP. FTIR spectra evidenced the interactions between polymeric components of blend films.